PENENTUAN DOSIS RADIASI EKSTERNAL PADA PEKERJA RADIASI DI RUANG PENYINARAN UNIT RADIOTERAPI RUMAH SAKIT DR.KARIADI SEMARANG - Widyaningsih, Dewi; Sutanto, Heri (BERKALA FISIKA, 2013)
Application of nuclear technology is very usefull but it is very risk for human health andsafety, therefore necessary to control of radiation for humans and the environment. For it hasbeen done on the monitoring of external radiation dose to radiations workers in the examinationroom of radiotherapy unit Dr.Kariadi Semarang hospital. The study was conducted by measuringradiation dose rate of examianation room and operator’s room using Surveymeter and monitoringexternal radiation dose of radiation workers using alarm personal dosimeter Rados. The resultsshowed that the highest radiation dose rate is below the head source is equal to 20 μSv / h.External radiation dose in radiation workers every month on average 33.84 μSv, then for one yearis estimated to be 0.406 mSv. This value is within the allowable limit according to the dose limitvalue set by ICRP and BAPETEN which should not exceed 20 mSv a year.Keywords: external radiation dose, dose limit value, radiation protection.